Performance of some civil engineering structures on Odukpani clay shale, Southeastern Nigeria - Abidemi Olujide Ilori; Anthony Michael George; Ini Christopher Umoh; Ediomo O. Eyakndue; Ubong Udoette Ukpekpe (Discover Geoscience)
Abstract The performance of pavement and bridges on a stretch of 21.4 km of Calabar—Itu highway is the focus of this study. Within this 21.4 km section, the pavement structure has completely failed while the three bridges within this section are still in good structural health as there is no failure of both superstructure and foundation. Three groups of shale soils characterize this stretch; these are Ekenkpon Nkporo, and New Netim Marl. The materials were characterized by both geotechnical and geophysical methods at shallow and deep surface. The Ekenkpon and Nkporo classifies as organic silt and clay with high plasticity (OH) and Inorganic silt, (MH) respectively, while New Netim marl classify as lean clay (CL). Geotechnical shear strength properties determined by Direct shear tests for Ekenkpon indicate cohesion value’C, of 36.1 kN/m2, angle of shearing resistance of 36.8°, that of Nkporo shale with cohesion value as 36 kN/m2 and angle of internal friction as 3.6°. Based on the shear strength properties, Ekenkpon shale has a bearing capacity of 3902.95 kN/m2, Nkporo shale has a value of 667.02 kN/m2, and New Netim Marl with a value of 319.75 kN/m2. Within the load range of 50 kN/m2 to 500 kN/m2 the compressibility values for Nkporo are between 0.29 and 0.23 per MPa, while that of Ekenkpon shale for the same load range is between 0.78 and 1.50 per MPa, showing Ekenkpon shale is highly compressible than the Nkporo shale. Shallow seismic refraction survey involving both p and s-waves were also deployed to evaluate the quality of soils at some locations along this alignment. Results indicate the near the surface horizon which serves as the foundation for highway pavement is composed of soil materials that are highly permeable, dispersive, collapsible, easily eroded as indicated by low Slake Durability Index with values between 6.9 and 51.42%; properties which are all dependent on changes in water content. Whereas at depth, the same soil sequence but stable as permeability to water is very low, hence the stability of bridge foundations in them.